Environmental Benefits of Domestic Solar Water Heating Systems - Kalogirou, Soteris A. (My University, 2005)
In this paper an analysis of the pollution caused by the burning of fossil fuels is briefly presented followed by a study on the environmental protection offered by domestic solar water heating systems. The results presented in this paper show that by using solar energy for domestic water heating considerable amounts of greenhouse polluting gasses are avoided. The savings, compared to a conventional system, are about 80%, with electricity or diesel backup and about 75% with both electricity and diesel backup. Additionally, all systems investigated give positive and very promising financial characteristics. With respect to life cycle assessment of the systems, the energy spent for the manufacture and installation of the solar systems is recouped in about 1.2 years, whereas the payback time with respect to emissions produced from the embodied energy required for the manufacture and installation of the systems varies from a few months to 3.7 years according to the fuel and the particular pollutant considered. Moreover the cost of damage avoided by some of the pollutants is investigated with respect to damages to crops, materials, mortality and morbidity. It was found that C£31 (Euro 51.7) are avoided per year when the system is using electricity as auxiliary, C£15.5 (Euro 25.8) are avoided when both electricity and diesel are used and C£13 (Euro 21.7) when diesel is used alone for each solar water heating system. It can therefore be concluded that solar energy systems offer significant protection to the environment and cost savings and should be employed whenever possible in order to achieve a sustainable future.
Keywords: Pollution; Fossil fuels; Energy; Domestic water heating